2009
DOI: 10.1094/cchem-86-3-0281
|View full text |Cite
|
Sign up to set email alerts
|

Germination of Wheat: A Functional Proteomics Analysis of the Embryo

Abstract: Cereal Chem. 86(3):281-289Germination in the soft wheat (Triticum aestivum L.) cultivar Rosella was followed for three days after imbibition by proteomic analysis of the germ tissue. Two-dimensional electrophoresis was performed in triplicate for proteins extracted from embryos dissected from mature grain and from grains germinated for 1, 2, and 3 days. For this period, 63 proteins (in 86 spots) in the germ were identified as decreasing in abundance, 35 proteins (in 60 spots) as increasing in abundance, and 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 39 publications
(44 reference statements)
5
25
0
Order By: Relevance
“…Previous proteomic analyses of rice and wheat embryos and different tissues of barley seeds have shown that most storage proteins and proteases/enzyme inhibitors are mainly localized in the endosperm/aleurone tissues, whereas those involved in translation and protein folding such as eIF5A1 and PDIs, and cellular signalling such as 14‐3‐3s and CRT, in the embryos (Bønsager et al ., ; Kim et al ., ; Mak et al ., ). These results suggest the tissue specificity of the related proteins identified in this study, which involved whole seed samples.…”
Section: Resultsmentioning
confidence: 97%
“…Previous proteomic analyses of rice and wheat embryos and different tissues of barley seeds have shown that most storage proteins and proteases/enzyme inhibitors are mainly localized in the endosperm/aleurone tissues, whereas those involved in translation and protein folding such as eIF5A1 and PDIs, and cellular signalling such as 14‐3‐3s and CRT, in the embryos (Bønsager et al ., ; Kim et al ., ; Mak et al ., ). These results suggest the tissue specificity of the related proteins identified in this study, which involved whole seed samples.…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, a probeset annotated in wheat as α‐amylase/trypsin inhibitor (designated as CM1 because of its solubility in Chloroform: Methanol) showed a twofold higher expression in D than AR seeds (Table S1). As a decrease in the mRNA and protein levels of trypsin and α‐amylase inhibitors was observed during wheat seed germination (Mak et al. , 2009; Potokina et al.…”
Section: Resultsmentioning
confidence: 99%
“…, 2009). Moreover, the germination of non‐dormant seeds is associated with down‐regulation of trypsin and α‐amylase inhibitor proteins at both transcript and protein levels (Mak et al. , 2009; Potokina et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipid and protein contents were higher in sprouted seeds soaked in zinc solution than in control seeds soaked in water. The evolution of these molecules during sprouting is mainly due to enzymatic mechanisms aiming to provide the embryo with nutrients . The increase in lipid and protein contents might be related to an effect of zinc on lipases and proteases: In fact, zinc plays a key role in structural and catalytic functions of numerous enzymes .…”
Section: Resultsmentioning
confidence: 99%